The New Construction Approach Adapted by Ashghal for the Public Projects in Qatar - Al-Buenain, Ahmad; Al-Muhanadi, Saeed; Falamarzi, Mohammad (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
The purpose of this paper is to review the new strategy adapted by Ashghal to implement lean construction in Qatar to improve project performance and predictability of delivery. This is a significant change programme led by a government delivery entity. In 2017, the Public Works Authority (ASHGHAL) piloted the implementation of lean construction principles within 3 projects. Following realization of tangible benefits through the pilot application, Ashghal made it contractual to implement lean in all future projects. Since then, Ashghal has awarded 26 projects with the enhanced requirements in the construction contracts. The enhanced requirements within the construction contract are intended for improving public satisfaction and project delivery performance. This paper discusses the changes implemented by Ashghal and provides some recommendations. The paper presents findings from Literature reviews, interviews with Ashghal, and site visit to one of the projects undergoing the transformation. Qatar had not implemented lean construction principles at such large scale before 2018. Ashghal has realised various challenges in embedding the new strategy, which will be explored in this paper. Ashghal recognizes that the program requires time and effort, and has invested in building local capability. The enhanced requirements are applicable only to full infrastructure construction projects awarded post October 2018. Thereby the new approach is focused on contractors and supervision consultants’ way of delivery. There is scope however to expand the application of lean principles to improve internal processes. Other influencing government agencies could also benefit from this program. Finally, this paper presents the efforts by Ashghal in raising the bar of delivery in the state of Qatar and the region. It is a rare example of a public sector authority leading a major change initiative that can benefit all parties involved and especially in construction, which makes this a very unique and special case that deserves to be written about.